Populism and Fiscal Illusion. (30th August 2018) - Davidson, Sinclair
Abstract: There is a widespread concern that anti‐elitist or populist opinion is on the rise. The policy concern is that political opportunists would exploit voter rational ignorance for their own cynical purposes. In this article I demonstrate that, in the field of taxation, this sort of behaviour already occurs. Fiscal illusion can be described as deceiving taxpayer‐voters into paying more tax than they would otherwise agree to. Taxpayers are already victims of political opportunism unrelated to the rise of populism.